2021
DOI: 10.2196/28044
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Differential Impact of an Internet-Based Mental Health Intervention on Outcomes of Well-being and Psychological Distress During COVID-19: Uncontrolled Intervention Study

Abstract: Background During COVID-19, the psychological distress and well-being of the general population has been precarious, increasing the need to determine the impact of complementary internet-based psychological interventions on both positive mental health as well as distress states. Psychological distress and mental well-being represent distinct dimensions of our mental health, and congruent changes in outcomes of distress and well-being do not necessarily co-occur within individuals. When testing inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 101 publications
3
23
0
1
Order By: Relevance
“…The study clearly demonstrated the anticipated significant improvements in mental well-being and resilience, confirming preliminary positive effects identified in a previous uncontrolled intervention study [ 36 ]. We found medium effect sizes for mental well-being, which is above the average typically reported in the literature [ 29 , 79 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The study clearly demonstrated the anticipated significant improvements in mental well-being and resilience, confirming preliminary positive effects identified in a previous uncontrolled intervention study [ 36 ]. We found medium effect sizes for mental well-being, which is above the average typically reported in the literature [ 29 , 79 ].…”
Section: Discussionsupporting
confidence: 84%
“…Given the tailored nature of the Be Well Plan that considers participants’ characteristics, needs, and preferences, there is the potential that the intervention also improves outcomes beyond mental health and well-being, such as self-efficacy, a sense of control, and cognitive flexibility. Although preliminary evidence for the Be Well Plan program’s impact has been established [ 36 ], there is a clear need now to establish its efficacy using a more robust methodological design.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have, at time of writing this manuscript, been completed, with further studies underway. The first completed study was an uncontrolled intervention study aimed at determining the initial impact of the intervention, finding significant improvements in outcomes of wellbeing, resilience, and psychological distress, most notably for those with more problematic mental health scores at baseline (van Agteren et al, 2021a). Preliminary findings of a randomised controlled study are replicating the positive findings of the first study, with a manuscript currently being prepared.…”
Section: Discussionmentioning
confidence: 99%
“…These two steps are outside the scope of this article, as the aim here is to describe the development and design process. The actual evaluation of the programme on outcomes will be covered in subsequent publications, including a pre-post pilot study in university students and general community members (n = 89;van Agteren et al, 2021a) and a randomised controlled study in university students. A brief description of the evaluation approach is provided in the discussion of this manuscript.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation